Nonlinear Mean Reversion In Real Exchange Rates: Evidence From The ASEAN-5 - Ahmad Zubaidi, Baharumshah; Liew, Khim Sen; Lau, Evan (Munich University Library, 2003)
Utilizing formal nonlinear unit root test (Sarno, The behavior of US public debt: a nonlinear perspective. Economics Letters 2001: 119 – 125), this study provides robust evidence of nonlinear mean reversion in the real exchange rates of 4 major ASEAN countries. We conclude that the bulk of the evidence based on conventional unit root tests may be biased against long run Purchasing Power Parity (PPP)